Occupational stress and its related demographic factors among Iranian CCU nurses: a cross-sectional study - Faraji, Azam (BMC Res Notes, 2019)
OBJECTIVES: Occupational stress can have an adverse effect on mental and physical health and performance of nurses. The aim of this study was to investigate the occupational stress of Iranian critical care unit (CCU) nurses and its related demographic factors. RESULTS: In this cross-sectional study, 155 CCU nurses were randomly selected. The Osipow Occupational Stress Questionnaire was used as data collection tool. The mean of nurses’ occupational stress was 210.13 ± 40.87 out of 300, which was at the “moderate-to-high” level. The highest mean of occupational stress was related to the subscale of “Role Overload” (36.30 ± 6.98) and the lowest mean was related to the subscale of “Physical Environment” (33.58 ± 9.76). There was no statistically significant difference between the mean occupational stress and variables of sex, age, academic degree and working experience.